Michael Ondaatje : haptic aesthetics and micropolitical writing - Marinkova, Milena (Continuum, 2011)
This study of selected literary and cinematic works by Michael Ondaatje investigates the political potential of the Canadian authors aesthetics. Contributing to current debates about affect and representation, ideology critique and the artwork, trauma and testimony, this book uses the concept of the haptic to demonstrate how Ondaatjes multisensory, fluid and historically inflected writing can forge an enabling relationship between audience, author and text. This is where Ondaatjes micropolitics, often misconstrued as ideologically suspect aestheticism, emerges: a praxis that intimates how one.